Penerapan Model Pembelajaran Take and Give dalam Meningkatkan Motivasi Dan Hasil Belajar IPA SMP Negeri 1 Afulu - Astiti Junior Hia; Samilinda Laia; Adil Hati Hulu (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
Low motivation and learning outcomes in Natural Science (IPA) are often caused by the implementation of conventional learning models that lack active student participation. This study aims to describe the improvement in learning quality, learning motivation, and learning outcomes in Science through the implementation of the Take and Give learning model at SMP Negeri 1 Afulu. This Classroom Action Research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 28 seventh-grade students in the even semester of the 2024/2025 academic year. The instruments used included observation sheets, learning quality questionnaires, learning motivation questionnaires, learning outcome tests, interview guides, and documentation. Data were analyzed descriptively quantitatively and qualitatively. The results showed a significant increase in all variables. Learning quality increased from 64.71% (sufficient category) in Cycle I to 98.60% (very good category) in Cycle II. Learning motivation increased from 67.00% (sufficient category) to 95.29% (very good category). The average learning outcome increased from 71.79 (sufficient category) to 82.68 (good category), with the learning completion percentage increasing from 67.86% to 89.29%. Hypothesis testing using a t-test for learning outcomes (t-test 5.164 > t-table 1.703) and a z-test for learning quality (z-test 3.83 > z-table 1.64) and learning motivation (z-test 3.33 > z-table 1.64) proved that the action hypothesis was accepted at the 5 percent significance level.